2020
DOI: 10.1088/1755-1315/418/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of clove oil from three forest clove accession groups in Maluku

Abstract: Forest cloves (Syzygium aromaticum (L.) Merr. & L. M. Perry.) are classified as wild and endemic clove to Maluku islands. So far, the studies on utilization of clove oil as an essential oil are still limited. This study aims to provide information on the physicochemical properties of clove oil from three clove accession groups in Maluku. Clove oil is obtained through the distillation of parts of the plant such as flowers bud, flower stalks, and leaves. The physicochemical components of clove oil in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
3
3
1
5
Order By: Relevance
“…Among the major compounds detected were Eugenol, 3‐Allyl‐6‐methoxyphenyl acetate, and Caryophyllene. This observation was in line with those reported in the literature (Mahulette, Yahya, and Wachjar, 2020). Mahulette, Yahya, and Wachjar (2020) presented that the main compound in the clove essential oil was Eugenol (20–28%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Among the major compounds detected were Eugenol, 3‐Allyl‐6‐methoxyphenyl acetate, and Caryophyllene. This observation was in line with those reported in the literature (Mahulette, Yahya, and Wachjar, 2020). Mahulette, Yahya, and Wachjar (2020) presented that the main compound in the clove essential oil was Eugenol (20–28%).…”
Section: Resultssupporting
confidence: 93%
“…This might be due to the mixture of air bubbles and essential oils in the steam stream of the system due to the high heating intensity required compared to the SEE method. Mahulette et al (2020) found that the specific gravity of clove oil was in a similar range to data observed in the present study. Besides, the extracted clove oil using SEE and THD had the highest density as presented in Table 1.…”
Section: Resultssupporting
confidence: 91%
“…Pengolahan bahan baku cengkih Hutan menjadi produk turunan yang lain seperti minyak atsiri (essential oil) belum dilakukan karena dianggap memiliki kadar minyak dan kadar eugenol yang rendah. Kadar minyak atsiri pada bagian bunga cengkih Hutan adalah sekitar ±20%, tangkai bunga ±20% dan daun ±21% (Mahulette et al 2019b(Mahulette et al , 2020a(Mahulette et al , 2019c. Rendahnya kadar minyak dan kadar eugenol menyebabkan produk utama yang dihasilkan sejauh ini hanya sebatas bunga cengkih kering (dry flower bud).…”
Section: Produk Dan Pasarunclassified
“…Salah satu spesies cengkih tipe liar yang mulai banyak diminati oleh petani terutama di wilayah sebarannya di Maluku adalah cengkih Hutan. Cengkih Hutan sebarannya luas di beberapa lokasi tertentu di Pulau Ambon (Desa Hitulama, Hitumesing) dan di Pulau Seram (Desa Latu dan Hualoi) (Mahulette et al, 2019a(Mahulette et al, , 2019c (Hariyadi et al 2020a(Hariyadi et al , 2019Mahulette et al 2019cMahulette et al , 2019bMahulette et al , 2020aMahulette et al , 2020bMahulette et al , 2019a.…”
unclassified
“…Forest clove is an endemic plant from the Maluku Islands (Hariyadi et al 2019;Mahulette et al 2020aMahulette et al , 2019bMahulette et al , 2020bMahulette et al , 2019a. The fast growth and robust root system allow the association of this clove with AMF (Hariyadi et al 2019;Mahulette et al 2019bMahulette et al , 2020a.…”
Section: Introductionmentioning
confidence: 99%